2019
DOI: 10.1155/2019/9140167
|View full text |Cite
|
Sign up to set email alerts
|

Robust SAR Automatic Target Recognition Based on Transferred MS-CNN with L2-Regularization

Abstract: Though Synthetic Aperture Radar (SAR) Automatic Target Recognition (ATR) via Convolutional Neural Networks (CNNs) has made huge progress toward deep learning, some key issues still remain unsolved due to the lack of sufficient samples and robust model. In this paper, we proposed an efficient transferred Max-Slice CNN (MS-CNN) with L2-Regularization for SAR ATR, which could enrich the features and recognize the targets with superior performance. Firstly, the data amplification method is presented to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Dai et al (2017) proposed a method for fundus image lesion recognition based on MS-CNN model, and found that the recognition accuracy of this method was 99.7% and the recall rate was 87.8% [6]. Zhai et al (2019) showed that data training in MS-CNN model could improve the extraction effect of robust features and avoid the occurrence of overfitting [7]. Therefore, in order to meet the demand of automatic recognition of commodities, and to improve the recognition efficiency and save costs, I conducted the research on intelligent CIR technology based on deep learning algorithm to meet the application demand of automatic recognition of individual merchants.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al (2017) proposed a method for fundus image lesion recognition based on MS-CNN model, and found that the recognition accuracy of this method was 99.7% and the recall rate was 87.8% [6]. Zhai et al (2019) showed that data training in MS-CNN model could improve the extraction effect of robust features and avoid the occurrence of overfitting [7]. Therefore, in order to meet the demand of automatic recognition of commodities, and to improve the recognition efficiency and save costs, I conducted the research on intelligent CIR technology based on deep learning algorithm to meet the application demand of automatic recognition of individual merchants.…”
Section: Introductionmentioning
confidence: 99%
“…where L(w) is the original Loss_Func, w i is the ith weight in the network, n is the total number of weights, and λ is the regularization strength. • L2 regularization: This technique adds a penalty to the Loss_Func proportional to the square of the weights, which encourages the model to have small weights and can help to prevent overfitting [115][116][117][118]. The regularized Loss_Func for L2 regularization can be written as:…”
Section: Regularization Techniquesmentioning
confidence: 99%
“…Compared with the fewest parameters-based networks for SAR image classification, this architecture was deeper with only about 10% of parameters. An efficient transferred max-slice CNN with L2-regularization term was proposed in [409] for SAR-ATR, which could enrich the features and recognize the targets with superior performance with small samples. An asymmetric parallel convolution module was constructed in [410] to avoid severe overfitting.…”
Section: A Sar Images Processingmentioning
confidence: 99%